5x(-4x+4)=1

Simple and best practice solution for 5x(-4x+4)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x(-4x+4)=1 equation:


Simplifying
5x(-4x + 4) = 1

Reorder the terms:
5x(4 + -4x) = 1
(4 * 5x + -4x * 5x) = 1
(20x + -20x2) = 1

Solving
20x + -20x2 = 1

Solving for variable 'x'.

Reorder the terms:
-1 + 20x + -20x2 = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 20x + -20x2 = 0

Begin completing the square.  Divide all terms by
-20 the coefficient of the squared term: 

Divide each side by '-20'.
0.05 + -1x + x2 = 0.0

Move the constant term to the right:

Add '-0.05' to each side of the equation.
0.05 + -1x + -0.05 + x2 = 0.0 + -0.05

Reorder the terms:
0.05 + -0.05 + -1x + x2 = 0.0 + -0.05

Combine like terms: 0.05 + -0.05 = 0.00
0.00 + -1x + x2 = 0.0 + -0.05
-1x + x2 = 0.0 + -0.05

Combine like terms: 0.0 + -0.05 = -0.05
-1x + x2 = -0.05

The x term is -1x.  Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
-1x + 0.25 + x2 = -0.05 + 0.25

Reorder the terms:
0.25 + -1x + x2 = -0.05 + 0.25

Combine like terms: -0.05 + 0.25 = 0.2
0.25 + -1x + x2 = 0.2

Factor a perfect square on the left side:
(x + -0.5)(x + -0.5) = 0.2

Calculate the square root of the right side: 0.447213596

Break this problem into two subproblems by setting 
(x + -0.5) equal to 0.447213596 and -0.447213596.

Subproblem 1

x + -0.5 = 0.447213596 Simplifying x + -0.5 = 0.447213596 Reorder the terms: -0.5 + x = 0.447213596 Solving -0.5 + x = 0.447213596 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 0.447213596 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 0.447213596 + 0.5 x = 0.447213596 + 0.5 Combine like terms: 0.447213596 + 0.5 = 0.947213596 x = 0.947213596 Simplifying x = 0.947213596

Subproblem 2

x + -0.5 = -0.447213596 Simplifying x + -0.5 = -0.447213596 Reorder the terms: -0.5 + x = -0.447213596 Solving -0.5 + x = -0.447213596 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -0.447213596 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -0.447213596 + 0.5 x = -0.447213596 + 0.5 Combine like terms: -0.447213596 + 0.5 = 0.052786404 x = 0.052786404 Simplifying x = 0.052786404

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.947213596, 0.052786404}

See similar equations:

| 18+9p12p-31= | | -13=2.7x-1.35x | | 16.331+m=38.478 | | 9g-47g-3= | | 24577=x-76x | | f(x)=8ln(x) | | 4x+2(7x+11)=112 | | 2b-6b+3= | | 13y-22y=12 | | 1000-1= | | (3+1/3)*(2+1/2)=x | | 10=4y+10+5y | | 4(f-5)-3=2f-3 | | (3+1/3)x(2+1/2)=x | | 35.7/5.24= | | (1-y)(3y+7)=0 | | (19b-6)-6(3b+2)=-2 | | 32x^2+40X-2016=0 | | 3p+2110p= | | h-79=83 | | 3w2w+6= | | (3x+5)-(9x-4)= | | p-0.20p=5 | | 2(1a+2a)= | | (8x+7)-(9x-8)= | | 21=3t | | 3ax-2=5ax-1 | | -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 |

Equations solver categories